FRI0157 Discrepancies Between Clinical and Antidestructive Effects of Rituximab in Rheumatoid Arthritis (RA). (9th June 2015) - Pivanova, A.V.; Lukina, G.V.; Sigidin, Ya.A.; Smirnov, A.V.; Kuzikyants, K.H.; Kuznetsova, A.Yu.; Nasonov, E.L.
Abstract : Background: Rheumatoid arthritis is a chronic autoimmune disease characterised by inflammation of the synovial tissue and destruction of the underlying cartilage and bone. The goal of antirheumatic treatment is not only to attenuate the clinical symptoms of joint inflammation, but also to inhibit the progression of joint destruction. Rituximab treatment slowed joint damage without clinical improvement. Noteworthy, clinical and antidestructive effects often did not coincide. Objectives: Comparison of clinical and antidestructive effect of Rituximab (RTX). Methods: Clinical and radiological study of 61 patients (pts) with RA (mean disease duration 10, 1±7, 7 years, mean DAS28 6, 3±0, 94, RF-positive 87%, ACCP-positive 93%) treated with RTX (1000 mgx2 or 500 mgx2). Clinical effect was assessed by EULAR criteria; radiological progression by SVH method. Results: Pronounced therapeutic effect of RTX was noted. By the 48-th week after receiving 2 courses of RTX good clinical response was registered in 29.7% (remissions – 14, 6%); good and satisfactory responses in 85.3%. Antidestructive effect of RTX was also significant. After 48 weeks of treatment progression of articular destruction was absent in all pts in clinical remission, in 83% of pts with low disease activity, and in 43% of pts with moderate activity. Narrowing of joint space was more pronounced than bone destruction – 32% and 25% respectively. Clinical and antidestructive effects often did not coincide. Noteworthy, RTX treatment slowed joint damage in 54% of pts without clinical improvement. There were no significant correlations between clinical outcomes and doses of RTX. The inhibition of radiological progression was more pronounced in pts treated with higher doses of RTX. Conclusions: Clinical and antidestructive results did not always coincide which suggests different mechanisms of clinical and antidestructive effects of anti-B-cell therapy. The therapeutic effect of different doses of RTX was practically the same but the antidestructive effect of higher doses was significantly greater. Disclosure of Interest: None declared